Income transfers and household debt. The advancing collateralization of social policy in the midst of restructuring crises - Lavinas, Lena (2024)
The aim of this article is to address how household debt and contemporary creditmarkets seem to be the defining elements in the reshaping of social policy both in developing and developed countries. We start off by recalling how the implementation of incomepolicies as the core of a new social protection paradigm has contributed to promote marketbasedfinance. We take Brazil as a case study to illustrate how this new connection betweenstate guaranteed income policies and credit markets has unfolded resulting in increasinghousehold debt. We show evidence that the connection between household debt and stateprovidedmonetary benefits is effective and significant. JEL Classification: E44; O11; O54.